Analisis Peranan Orang Tua dalam Pendampingan Belajar dari Rumah pada Siswa Kelas IV SD Negeri 1 Gubug - Himmatul Ulya; Eka Sari Setianingsih; Mila Karmila (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This research aims to find out the role of parents of students of grade IV SDN 1 Gubug in accompanying children learning from home whose implementation appears obstacles so that it has an impact on learning outcomes. This research method is descriptive qualitative research with the main subject being the parents. Based on the results of research analysis whose data collection using interview techniques, observations, questionnaires, and documentation obtained the results that parents of students of grade IV SDN 1 Gubug maximum carry out their role accompanying children to learn from home. The mentoring category is Very Good with a percentage of ˃81%. Learning assistance by parents is: as a learning guide, facilitator, motivator, and creating learning condusivity. Parents have difficulty accompanying learning. The category of constraints is "Low" with a percentage of ≤60% caused by: educational background, economic limitations, time manajemen, lack of material understanding, busy work, and crowds due to the large number of people at home. So that the implementation of mentoring and constraints related to students' online learning outcomes shows 55.6% of students get an average score of 81-90 and the category of learning outcomes is good.